2020
DOI: 10.1038/s41598-020-68566-2
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dysfunction impairs osteogenesis, increases osteoclast activity, and accelerates age related bone loss

Abstract: The pathogenesis of declining bone mineral density, a universal feature of ageing, is not fully understood. Somatic mitochondrial DNA (mtDNA) mutations accumulate with age in human tissues and mounting evidence suggests that they may be integral to the ageing process. To explore the potential effects of mtDNA mutations on bone biology, we compared bone microarchitecture and turnover in an ageing series of wild type mice with that of the PolgA mut/mut mitochondrial DNA ‘m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 79 publications
2
36
0
2
Order By: Relevance
“…This work highlights the correlation between accumulating mitochondrial respiratory chain deficiency and advancing age in human osteoblasts. The PolgA mut /PolgA mut mouse model showed evidence of premature osteoporosis and associated osteoblast respiratory chain deficiency was confirmed previously and shown to be associated with declining bone density 24,25 . In vivo assays demonstrated significant defects in bone formation by ostoeblasts with reduced osteoblast numbers, increased osteoclast numbers, and in vitro assays demonstrated increased resorption activity by osteoclasts.…”
Section: Discussionsupporting
confidence: 68%
“…This work highlights the correlation between accumulating mitochondrial respiratory chain deficiency and advancing age in human osteoblasts. The PolgA mut /PolgA mut mouse model showed evidence of premature osteoporosis and associated osteoblast respiratory chain deficiency was confirmed previously and shown to be associated with declining bone density 24,25 . In vivo assays demonstrated significant defects in bone formation by ostoeblasts with reduced osteoblast numbers, increased osteoclast numbers, and in vitro assays demonstrated increased resorption activity by osteoclasts.…”
Section: Discussionsupporting
confidence: 68%
“…Indeed, lack of oxygen delivery to the cells due to blood supply deprivation has a significant impact on the cellular production of energy for the tissue during the healing process (from protein synthesis to cell migration and neovascularization) [ 4 , 5 , 6 , 7 , 8 , 9 ]. A growing body of evidence has demonstrated that mitochondrial dysfunction impairs osteogenesis [ 10 ] and that this organelle may be a target for new therapeutic options to treat metabolic bone diseases [ 11 ]. It has been demonstrated that direct delivery of adenosine triphosphate (ATP) to the cells improves tissue healing in rabbit [ 7 ] and mouse [ 8 ] models.…”
Section: Introductionmentioning
confidence: 99%
“…However, 950 nm NIR PBM increased mitochondrial mass, which is decreased during thawing, and reduced mitochondrial ROS. Mitochondrial dysfunction inhibits osteogenesis, increases osteoclast activity, and accelerates age-related bone loss 24 . The activity of mitochondria recovered by 950 nm NIR PBM increases ALP activity, a marker of differentiation, the ultimate goal of stem cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidants usually used to reduce oxidative stress during thawing cells showed limitations in recovering mitochondrial activity. Since the predominant PBM mechanism is the activation of CCO as a photoreceptor in mitochondria, we hypothesized that PBM on thawing stem cells could restore mitochondrial function and differentiation potential 24 . We confirmed that PBM has a positive effect on cryodamaged stem cells and established the hypothesis that increased oxygen consumption of CCO increases mitochondrial activity.…”
Section: Introductionmentioning
confidence: 99%